Choosing connection: relational values as a career choice motivation predict teachers’ relational goal setting - Oberhauser, Lia; Hertel, Silke (Frontiers in Psychology, 2023)
Relational goals have a positive impact on teachers’ classroom performance, but little is known about the antecedents of these goals. One of the most important reasons for choosing teaching as a career is the desire to work with children/adolescents. This study examined this reason along with other relational career choice motives as predictors of relational goal orientation, complementing other studies that have examined the relationship between reasons for career choice and goal orientations but did not consider the relational component. We hypothesized that relational motives for career choice would predict relational goal setting for teaching better than other reasons for career choice. The sample comprised N = 167 student teachers at a large German university who answered an online questionnaire assessing motivations for choosing teaching as a career, professional self-concepts and relational goal orientation. Adopting an expectancy-value perspective, we set up a structural equation (N = 167) and two linear regression models (n1 = 86, n2 = 81) to examine the effects of student teachers’ career choice motives on relational goal orientation. Analyses showed that the relational motive of educational interest was the only significant predictor in a structural equation model with educational interest, subject-specific interest, and general ability beliefs as predictors and relational goal orientation as the criterion. The first regression model found that the social utility motive work with children/adolescents was a significant predictor of relational goal orientation when combined with other career choice motives, namely educational interest, subject-specific interest, general abilitiy beliefs, and three other social utility factors. The second regression model found no significant effects of educational interest, subject-specific interest, educational self-concept and subject-specific self-concept on relational goal orientation. The results suggest that teachers who choose their profession because they enjoy working with children and adolescents are likely to strive to build satisfactory student-teacher relationships. Implications for future research and teacher education are discussed.